Development of a Novel Three Phase Grid-Tied Multilevel Inverter Topology - Mirza Mohammad Shadab; Mohammad Arifuddin Mallick; Mohammad Tufail; M. S. Jamil Asghar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The conventional line-commutated ac-to-dc converters/ inverters have square-shaped line current. It contains higher-order harmonics which generates EMI and it causes more heating of the core of distribution or power transformers. PWM based inverters using MOSFET/IGBT have higher switching losses, and the power handling capability and reliability are quite low in comparison to thyristors/ SCR. A thyristor based forced commutated inverters are not suitable for PWM applications due to the problems of commutation circuits. A pure sinusoidal voltage output or waveform with low harmonic contents is most desirable for ac load using dc to ac conversion. This paper presents a new multilevel inverter topology in which three phase ac- to-dc converter circuits are used in inversion mode by controlling the switching angle. Due to natural commutation, no separate circuit is required for synchronization. In this paper simulation and analysis are done for grid-tied three-phase 6-pulse, Two three-phase, 3-pulse and 12-pulse converter. These converters are analysed for different battery voltage and different switching angle combinations in order to reduce the total harmonic distortion (THD). Three-phase harmonic filters are further added to the grid side to reduce the harmonic content in the line current. A comparative study of these converters is also presented in this paper.